Avaliação de diferentes técnicas de pulverização com base em agricultura de precisão - Jobim, Lucas dos Santos (2017)
The Precision Agriculture process proposes and implements spraying automation and control systems in agricultural machines, a system widely used and universal in the most diverse agricultural cultures. This work evaluates the efficiency of the application among the different spraying techniques that use Precision Agriculture technology, such as tractors (terrestrial), self-propelled (terrestrial) and aircraft (aerial), with a comparative purpose of items such as precision of application, speed of work, drops deposition and operational cost. The research region is located in the Municipality of Cachoeira do Sul, central region of Rio Grande do Sul, where agricultural activity has intense participation. The project was developed in an experimental area located in the interior of the Municipality of Cachoeira do Sul. Applications of chemical pesticides were made using three different techniques, all of which are based on the use of Precision Agriculture technology. The spraying techniques that are being evaluated are the terrestrial tratorized, terrestrial self-propelled and aerial, being the methodology based on evaluation of the accuracy of the GPS system, drop drops on the target (hydrosensitive cards), working time, cost of acquisition of machines and outsourcing (based on local budget research). The accuracy results of the navigation systems were more favorable for the self-propelled sprayer, followed by the tractor and in the airplane sequence, but both evaluated systems maintained the standardized average of precision of each navigation system. Regarding droplet deposition on the target, self-propelled spraying was more efficient (greater target arrival and less drift). In relation to the working time, aerial spraying showed much higher speed, followed by self-propelled and lastly the tratorized system. As for the equipment acquisition costs, they were sequentially expressed in decreasing order starting with the agricultural aircraft, self-propelled sprayer and tractor, and the average cost of outsourcing services remained tied between the self-propelled and aerial application and the tractor system if it showed more expensive than the others. In this way, it is concluded that the best spray system is that it adapts to the field condition and expenditure of financial investment, according to the reality of the producer.